Design and Manufacture of Electric Car Chasis Frame for Two Passengers With Solidworks Modeling 2020 - Ahmad Zaenuri; Ade Sunardi; Kasum Kasum (Journal of Global Engineering Research and Science, 2022)
An electric car is a car that is driven by a DC motor using energy stored in the battery. The use of electric cars is considered more effective in addition to not causing air pollution and a simpler engine construction and as an alternative means of transportation. The frame/chassis is the main part of the car that functions to support other components such as the engine, battery, steering system, braking system, driver's seat and other vehicle equipment, and also as a vibration damper if the vehicle runs on various types of road surfaces and various modes of motion. From the vehicle, the frame used is a ladder frame which has a simpler and stronger structure. This study aims to design and manufacture the frame of an electric car and analyze the load received and the maximum load that the frame can withstand. This research begins with the design of the frame, then the assembly of the frame will be carried out then data will be collected on the frame which will then be processed to determine the load received by the frame and analyze the value of the welding stress on the frame.